Mining the Inner Experience: A Qualitative Study of Utilizing Mind Maps in Group Work. Issue 3 (3rd July 2021) - Rowell, P. Clay; Shannonhouse, Laura; Galloway, Amaris; Garner, Zachary D.
ABSTRACT: The authors explored the impact of a nine-week group experience on counselor-trainees by analyzing their weekly mind maps using consensual qualitative research. The participants' subjective, inner experiences revealed through the mind maps are shared. Implications for group work and counselor education, and recommendation for future research, are provided.